Thromboembolic events associated with immunoglobulin treatment. Issue 1 (9th February 2013) - Funk, M. B.; Gross, N.; Gross, S.; Hunfeld, A.; Lohmann, A.; Guenay, S.; Hanschmann, K. M.; Keller‐Stanislawski, B.
<x xml:space="preserve">Abstract</x> Objective Due to an increasing number of reported thromboembolic events (TEE) after the administration of one intravenous immunoglobulin (IVIG) and one subcutaneous immunoglobulin (SCIG), pharmacovigilance and laboratory data were collected to analyse the root cause and assess the reporting frequency of TEEs for various IG products. Methods Paul‐Ehrlich‐Institut retrospectively analysed 228 reports of TEEs associated with six different IG products and estimated annual TEE‐reporting rates based on worldwide sale figures over a period of 6 years (2006–2011). In addition, non‐activated partial thromboplastin time (NAPTT) testing was performed to capture pro‐coagulant potential of six IG products (four IVIG and two SCIG). Results For three IVIGs, the drug‐related TEE‐reporting rates remained stable from 2006 to 2011 (0–0·83 cases per 1000 kg IVIG distributed). In contrast, the TEE rate of one IVIG increased significantly from 0·33 cases in 2006 to nearly nine cases in 2010 (P < 0·001). The NAPTT testing of IG products with a low TEE rate revealed a NAPTT time >200 s and a NAPTT ratio >0·8, whereas TEE‐associated batches of IG products with an increased TEE rate had a NAPTT ratio <0·8. After modifications of manufacturing processes, a normalization of NAPTT results and a decrease in TEE rates could be demonstrated.